2020
DOI: 10.1080/21691401.2020.1726937
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DDX11-AS1 facilitates gastric cancer progression by regulating miR-873-5p/SPC18 axis

Abstract: Gastric cancer (GC) is a malignant tumour with high lethality. Accruing evidence elucidates the critical adjusting role of long non-coding RNA (lncRNAs) in human cancers. DDX11 antisense RNA 1 (DDX11-AS1) was previously found to be involved in GC pathogenesis. However, the precise molecular mechanisms of DDX11-AS1 need to be further investigated. In this study, we found that DDX11-AS1 expression was up-regulated in GC tumour tissues and cells. Increased DDX11-AS1 expression was associated with advanced TNM sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…22 Furthermore, lncRNA TDRG1 and lncRNA DDX11-AS1 accelerated the aggressiveness of GC by sponging miR-873-5p. 24,25 Herein, miR-873-5p was lowly expressed in infiltrative GC tissues.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…22 Furthermore, lncRNA TDRG1 and lncRNA DDX11-AS1 accelerated the aggressiveness of GC by sponging miR-873-5p. 24,25 Herein, miR-873-5p was lowly expressed in infiltrative GC tissues.…”
Section: Discussionmentioning
confidence: 93%
“… 23 In addition, miR-873-5p acts as a tumor-inhibiting molecular in GC. 24 , 25 However, the regulatory mechanism of miR-873-5p in GC growth pattern is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another research disclosed that miR-873-5p reduced cell invasion and migration through targeting CXCL16 in papillary thyroid cancer [18]. In GC, miR-873-5p expression could be inhibited by lncRNA TDRG1 or lncRNA DDX11-AS1, thereby accelerating the aggressiveness of GC [20,21]. Herein, miR-873-5p expression had a negative correlation with circVPS33B in in ltrative GC tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that miR-873-5p played an inhibitory role in numerous cancers development, such as glioma [17], papillary thyroid cancer [18], and colorectal cancer [19]. Moreover, miR-873-5p was uncovered to curb the malignancy of GC cells [20,21]. However, the mechanism of miR-873-5p in in ltrative GC progression has not been fully clari ed.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] For example, the expression of lncRNA DDX11-AS1 is up-regulated in GC tissues, and functionally, DDX11-AS1 facilitates GC progression by inhibiting miR-873-5p expression. 24 LncRNA FTX expression in GC is also up-regulated, and FTX can promote GC proliferation and invasion by adsorbing miR-144 and up-regulating ZFX; 25 conversely, as a tumor suppressor, lncRNA HAND2-AS1 inhibits the proliferation and migration of GC cells through modulating miR-590-3p/KCNT2 axis. 26 In this study, we verified that CTBP1-AS2 was a molecular sponge for miR-139-3p.…”
Section: Discussionmentioning
confidence: 99%